Spatiotemporal analysis of predation by carabid beetles (Carabidae) on nematode infected and uninfected slugs in the field. - Bjørn Arild Hatteland; Solveig Haukeland; Steffen Roth; May Bente Brurberg; Ian P Vaughan; William O C Symondson (PLoS ONE, 2013)
The dynamics of predation on parasites within prey has received relatively little attention despite the profound effects this is likely to have on both prey and parasite numbers and hence on biological control programmes where parasites are employed. The nematode Phasmarhabditis hermaphrodita is a commercially available biological agent against slugs. Predation on these slugs may, at the same time, result in intraguild predation on slug-parasitic nematodes. This study describes, for the first time, predation by carabid beetles on slugs and their nematode parasites on both spatial and temporal scales, using PCR-based methods. The highest nematode infection levels were found in the slugs Deroceras reticulatum and Arion silvaticus. Numbers of infected slugs decreased over time and no infected slugs were found four months after nematode application. The density of the most abundant slug, the invasive Arion vulgaris, was positively related to the activity-density of the carabid beetle, Carabus nemoralis. Predation on slugs was density and size related, with highest predation levels also on A. vulgaris. Predation on A. vulgaris decreased significantly in summer when these slugs were larger than one gram. Predation by C. nemoralis on slugs was opportunistic, without any preferences for specific species. Intraguild predation on the nematodes was low, suggesting that carabid beetles such as C. nemoralis probably do not have a significant impact on the success of biological control using P. hermaphrodita.